2014
DOI: 10.1038/srep05627
|View full text |Cite
|
Sign up to set email alerts
|

Bird fruit preferences match the frequency of fruit colours in tropical Asia

Abstract: While many factors explain the colour of fleshy fruits, it is thought that black and red fruits are common in part because frugivorous birds prefer these colours. We examined this still controversial hypothesis at a tropical Asian field site, using artificial fruits, fresh fruits, four wild-caught resident frugivorous bird species, and hand-raised naïve birds from three of the same species. We demonstrate that all birds favored red artificial fruits more than yellow, blue, black and green, although the artific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 48 publications
2
60
0
Order By: Relevance
“…We recovered three clusters and these fell into two major groups: the mammalassociated colours (which we treated as a single category in our three-category scheme) and the bird-associated colours (which are arrayed along an axis between black and red; Figure 2). Red fruits tend to be preferred by birds over other colours (Camargo et al, 2013;Duan, Goodale, & Quan, 2014;Schmidt et al, 2004), which might result in more rapid range expansion in red-fruited species. Similar findings have recently been reported using a very different methodology (Bergeron & Fuller, 2018), suggesting that, despite the potential problems with relying on human vision, broad patterns such as those identified here are based on real biological differences.…”
Section: P-value Of Latitudementioning
confidence: 99%
“…We recovered three clusters and these fell into two major groups: the mammalassociated colours (which we treated as a single category in our three-category scheme) and the bird-associated colours (which are arrayed along an axis between black and red; Figure 2). Red fruits tend to be preferred by birds over other colours (Camargo et al, 2013;Duan, Goodale, & Quan, 2014;Schmidt et al, 2004), which might result in more rapid range expansion in red-fruited species. Similar findings have recently been reported using a very different methodology (Bergeron & Fuller, 2018), suggesting that, despite the potential problems with relying on human vision, broad patterns such as those identified here are based on real biological differences.…”
Section: P-value Of Latitudementioning
confidence: 99%
“…Using ecological approaches, many studies have analysed associations between frugivore preferences and the frequency of different fruit colours in different regions (e.g. Duan, Goodale, & Quan, ; Herrera, ; Janson, ; Lomáscolo & Schaefer, ; Schaefer, Valido, & Jordano, ; Voigt et al, ; Willson, Irvine, & Walsh, ). However, few studies (if any) have used a phylogenetic approach to test whether different fruit colours affect large‐scale patterns of plant dispersal and distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Ecological studies suggest that birds often prefer red fruit (e.g. Duan et al, ; Shanahan, So, Gompton, & Gorlett, ) or darker coloured fruit (Schaefer et al, ). In a phylogenetic study of Coprosma (Rubiaceae), the authors noted that many dispersal events were by red‐fruited lineages, and they suggested that this pattern might be related to bird dispersal (Cantley, Markey, Swenson, & Keeley, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Willson et al 1990;Lord et al 2002;Stournaras et al 2013;Duan et al 2014). Fruits eaten by birds are often red or black and rarely orange, yellow, green or brown (Janson 1983;Willson et al 1989).…”
Section: Background Informationmentioning
confidence: 99%